The problem of participation the British team at the Olympic Games in 1980 - Viktoriia Sadykova (Cхід, 2013)
This article is devoted to the Summer Olympics in Moscow in 1980, specifically, the issue of participation the team from Great Britain, which was manifested in the "boycott the Olympics". Paid attention to display the main cause of the boycott and study the role of the British and American governments in its organization.